Penerapan RFID Dalam Pendataan Kehadiran Pegawai Negeri Sipil Berbasis Arduino - Andreas Aman Tokan; Iskandar Fitri; Rini Nuraini (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
In today's modern era, the development of technology and informatics is not something foreign to the public. As currently, RFID and Microsoft Excel technology can be used to overcome problems in everyday life such as student attendance or employees in private and government-owned agencies, security systems, parking systems, and can be used to monitor various reports on inventory that can be known in real time. time either by online or by synchronizing data, so the development of RFID technology cannot be doubted. However, the development of technology in Indonesia itself has not been fully evenly distributed where there are some areas that still do not apply this technology as a tool for daily activities, there are still a lot of regions that collect employee attendance still use the para or signature method, this of course can lead to fraud committed by unscrupulous employees for personal gain. The purpose of this study is to optimize and reduce attendance manipulation of sub-district office employees, because there are still a lot of government agencies, especially local government agencies that still perform attendance manually, such as the Witihama sub-district office. Witihama District is one of the sub-districts in eastern Indonesia, precisely in East Flores Regency, East Nusa Tenggara which still uses the employee initials method, so a technology such as RFID is needed to support the work of employees because this technology is very effective. The function of using RFID is to validate attendance and the function of Microsoft Excel itself is a media of information and attendance monitoring system directly and accurately by the disciplinary commission of the sub-district office.